Geochemical transformations beneath man-made ponds: Implications for arsenic mobilization in South Asian aquifers. (1st November 2020) - Stahl, Mason O.; Badruzzaman, A.B.M.; Tarek, Mehedi Hasan; Harvey, Charles F.
Abstract: The role of man-made ponds on arsenic mobilization was examined in Bangladesh. Here, we describe a field experiment that shows how recharge from a newly constructed pond creates a reactive front that moves downward into the underlying aquifer, but only advances slowly, less than 8 cm/year. We found that pond recharge introduces organic carbon that likely drives the reduction of sulfate and solid-phase iron. However, over the six-year period of the study the pond did not drive arsenic contamination of the underlying groundwater. An electron balance indicates that significant precipitation of ferrous iron and sulfide minerals may immobilize arsenic despite the shift towards more reducing conditions, explaining the very low observed aqueous arsenic concentrations. We additionally found that the amount of solid-phase electron acceptors available in the shallow sediments strongly retards the advance of a reduced sediment front. Our results suggest that labile organic carbon introduced by man-made ponds is efficiently mineralized in the sediments immediately below the pond bottom and thus is unlikely to drive arsenic mobilization deeper within the aquifer. We suggest that the excavation of man-made ponds removes young surficial sediments, leaving aged and less reactive sediments beneath the pond, so that recharge through excavated ponds does not mobilize arsenic at the high rates observed in recharge through natural wetlands and river banks.